A Review on Recent Trends in Photo-Drug Efficiency of Advanced Biomaterials in Photodynamic Therapy of Cancer - Ali, Nawab; Rasheed, Liaqat; Rehman, Wajid; Naseer, Muhammad; Khan, Momin; Hassan, Safia; Zulfiqar, Amina (Mini Reviews in Medicinal Chemistry, 2025)
Photodynamic Therapy (PDT) has emerged as a highly efficient and non-invasive cancer treatment, which is crucial considering the significant global mortality rates associated with cancer. The effectiveness of PDT primarily relies on the quality of the photosensitizers employed. When exposed to appropriate light irradiation, these photosensitizers absorb energy and transition to an excited state, eventually transferring energy to nearby molecules and generating Reactive Oxygen Species (ROS), including singlet oxygen [1O2]. The ability to absorb light in visible and near-infrared wavelengths makes porphyrins and derivatives useful photosensitizers for PDT. Chemically, Porphyrins, composed of tetra-pyrrole structures connected by four methylene groups, represent the typical photosensitizers. The limited water solubility and bio-stability of porphyrin photosensitizers and their non-specific tumor-targeting properties hinder PDT effectiveness and clinical applications. Therefore, a wide range of modification and functionalization techniques have been used to maximize PDT efficiency and develop multidimensional porphyrin-based functional materials. Recent progress in porphyrin-based functional materials has been investigated in this review paper, focusing on two main aspects including the development of porphyrinic amphiphiles that improve water solubility and biocompatibility, and the design of porphyrin-based polymers, including block copolymers with covalent bonds and supramolecular polymers with noncovalent bonds, which provide versatile platforms for PDT applications. The development of porphyrin-based functional materials will allow researchers to significantly expand PDT applications for cancer therapy by opening up new opportunities. With these innovations, porphyrins will overcome their limitations and push PDT to the forefront of cancer treatment options.
Keywords: apoptosis